2002
DOI: 10.1103/physrevb.65.104415
|View full text |Cite
|
Sign up to set email alerts
|

Strongly disordered spin ladders

Abstract: The effect of quenched disorder on the low-energy properties of various antiferromagnetic spin ladder models is studied by a numerical strong disorder renormalization group method and by density matrix renormalization. For strong enough disorder the originally gapped phases with finite topological or dimer order become gapless. In these quantum Griffiths phases the scaling of the energy, as well as the singularities in the dynamical quantities are characterized by a finite dynamical exponent, z, which varies w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
2

Year Published

2002
2002
2012
2012

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(74 citation statements)
references
References 55 publications
5
67
2
Order By: Relevance
“…Melin et al 22 used the RSRG method as well as the density-matrix RG method to study the distribution of the energy gap separating the ground and first excited states in clusters ͑with lengths up to 512͒ of AF two-leg spin-1/2 ladders. They found that the dynamic exponent z that characterizes this distribution is nonuniversal and depends continuously on the randomness strength.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Melin et al 22 used the RSRG method as well as the density-matrix RG method to study the distribution of the energy gap separating the ground and first excited states in clusters ͑with lengths up to 512͒ of AF two-leg spin-1/2 ladders. They found that the dynamic exponent z that characterizes this distribution is nonuniversal and depends continuously on the randomness strength.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…There are random quantum systems in which z depends on the initial disorder and z is approximately proportional to 1/α. This can be found, among others for random Heisenberg spin ladders [8]. In other systems with frustration, z is disorder independent (see the three-dimensional spin glass models [10]), and large spins are formed in these cases, as discussed in the following section.…”
Section: Strong Disorder Fixed Pointmentioning
confidence: 83%
“…There is singlet formation if S 1 = S 2 are coupled antiferromagnetically, in which case the pair of spin S 1 and S 2 is eliminated and the renormalized couplings are calculated by second order perturbation theory. The expression of the renormalized couplings can be found in the literature [7,8,10,14].…”
Section: Heisenberg Modelmentioning
confidence: 99%
See 2 more Smart Citations